If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 = -8 + 3x + 23 Reorder the terms: 3 + 6x = -8 + 3x + 23 Reorder the terms: 3 + 6x = -8 + 23 + 3x Combine like terms: -8 + 23 = 15 3 + 6x = 15 + 3x Solving 3 + 6x = 15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + 6x + -3x = 15 + 3x + -3x Combine like terms: 6x + -3x = 3x 3 + 3x = 15 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + 3x = 15 + 0 3 + 3x = 15 Add '-3' to each side of the equation. 3 + -3 + 3x = 15 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = 15 + -3 3x = 15 + -3 Combine like terms: 15 + -3 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| P=2l+2wforp | | (-4)p+(-3)(1-p)=3p+(-5)(1-p) | | 6x+10=4y | | e*x+3=21 | | S=4x^2-16x+88 | | x+7-4(x-1)=-10 | | x^2+7-10=0 | | 3y-4.6=20 | | 2x^4+11x-63=0 | | y=150*1.0894 | | -5(9+6x)=315 | | 40+3n=-23 | | f(x)=x^2-2+8 | | 72x+y=90 | | 5x+10=-22 | | 5(5x^2-6x+8)=0 | | 5x-8=2y+5 | | -2(-4x+6)=20 | | C=4c-6 | | 4(5-2n)-3n=4n-85 | | 4x(-7)=(-27) | | 0=5*cos(x) | | (-2x)+5=(-9) | | 8x+112=42 | | 11.4=8y | | (-11)=8x+13 | | 0=5*cosx | | 50/6-1/4=3/8 | | Y^2+4y+4-9y^2=0 | | 7x+17=25 | | 5c+4a+c= | | d=71 |